As good as my word: a memoir - Chandrasekhar, K. M. (Gurugram Harper Collins, 2022)
In this autobiography, he paints an intimate picture of the UPA government during one of its toughest phases and his own, crucial, role in steering India through some of her most severe crises - the Great Recession of 2008, the oilmen's strike in 2009 and the 26/11 Mumbai attacks - and scams - the 2G Spectrum case and the 2010 Commonwealth Games corruption scandal.
Keywords: Shashi Tharoor